Immunological tolerance ; mechanisms and potential therapeutic applications - Katz, David H.; Benacerraf, Baruj, 1920-2011 (Academic Press rapid manuscript reproductions., 1974)
Immunological Tolerance: Mechanisms and Potential Therapeutic Applications documents the proceedings of a conference held at Brook Lodge, Michigan, April 27-May 1, 1974. The conference brought together many of the investigators who have actively contributed to furthering knowledge and understanding of immunological tolerance. It will be immediately clear to the reader that the conference was structured in a way to consider phenomena of tolerance and immune suppression as interrelated entities with a certain degree of emphasis on the possible common cellular mechanisms involved.